Belize Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2016)
Belize has a rich history that dates back thousands of years. The country was first inhabited by the Mayans with records of their presence dating from 1500 BC. The first recorded European settlement was established circa 1638 by the British who called the country the Colony of British Honduras. The official name of the territory was changed from British Honduras to Belize in June 1973, and full independence was granted on September 21, 1981. There were several obstacles in the path toward independence, as illustrated by Guatemala's long-standing claim to the entire territory. It was only in November 1980, after several frustrated negotiations with Guatemala that Belizean diplomacy managed to obtain international support that led to the United Nations passing of a resolution that demanded the independence of Belize, but it was only in 1992 that Guatemala formally recognized Belize’s independence. After independence, Belize successfully implemented a development strategy which emphasized economic diversification and private sector development at a time where the terms of trade were favorable to the country. As a small, open economy, that is also extremely vulnerable to climate change and natural disasters, Belize’s ability to promote faster poverty reduction and greater shared prosperity will depend on how well the country deals with its main sources of vulnerability. In addition to weaknesses in infrastructure and in the skills of the labor force, several studies have pinpointed crime and violence and problems in the financial sector as important deterrents to growth. The analysis in this report confirms the centrality of these two factors. The predicament in the financial sector is largely driven by the small economic size of the country and the lack of competition in the banking sector, a common feature in small state economies that limits the availability of credit to small and medium enterprises. Stability issues in the sector complicate matters as these impose non-negligible risks to the health of the financial sector. On the other hand, the rise in the inflow of migrants from neighboring Central American countries with a history of crime and violence has been raised as a potential cause for high crime rates in Belize, but there is not enough evidence to substantiate that claim at this point. Policy interventions that could help halt the rise in criminality rates include ramping up the quality of education, keeping children at school, promoting education equivalency programs and job training, besides more direct approaches such as investing in safe neighborhood programs.